On the borderline of diabetes: understanding how individuals resist and reframe diabetes risk. (17th February 2021) - Howells, Kelly; Bower, Peter; Burch, Patrick; Cotterill, Sarah; Sanders, Caroline
Abstract : Medical sociologists highlight diagnosis as a critical moment in understanding the illness experience and have extended analysis to the growing focus on 'predisease states' in relation to policy and medical practice. The biomedicalisation of diabetes risk, labelled as 'prediabetes', is one predisease area Public Health England have prioritised via the roll-out of a national diabetes prevention programme (NDPP). The label and language of prediabetes frames this risk as a medical condition and this could have both social and practical consequences for how individuals manage this risk. Through data drawn from individual interviews and observations, we explore how individuals respond to the label of prediabetes and how they interpret and respond to their 'at-risk' status. The findings demonstrate that for some participants, the framing of risk seemed consistent with a biomedical paradigm as reflected within clinical discussions and the language used. For others, previous knowledge or experiences were drawn upon to resist, downplay and reframe their at-risk status. Our analysis reflects varying degrees of resistance where for some this seemed to mitigate against the threat of 'biographical disruption' associated with the risks of developing future diabetes. In such cases, respondents also resisted the notion that they were 'candidates'. However, in some cases, there was little resistance to the label of prediabetes, yet the perceived risk was 'low' in the context of competing health priorities or in relation to their expectations of health status in older age. Across participants, these varied responses were reflected in corresponding resistance to key messages promoting health behaviour change.